Differential control and calcium-dependence of production of endothelium-derived relaxing factor and prostacyclin by pig aortic endothelial cells. - White, D. G. (1989)
1. Production of endothelium-derived relaxing factor (EDRF) by primary cultures of pig aortic endothelial cells was assessed indirectly by measuring endothelial cyclic GMP content, and prostacyclin production was measured by radioimmunoassay of 6-keto prostaglandin F1 alpha (6-keto PGF1 alpha). 2. The resting level of cyclic GMP fell significantly following removal of extracellular calcium (1 mM EGTA present), but elevations of cyclic GMP content induced by sodium azide (10 microM) or atriopeptin II (10 nM) were similar in the absence and presence of extracellular calcium. 3. Haemoglobin (10 microM) reduced the resting level of cyclic GMP in the presence, but not the absence of extracellular calcium. M&B 22,948 (100 microM), superoxide dismutase (30 u ml-1), bradykinin (0.1 microM), ATP (10 microM) and ionophore A23187 (0.1 microM) each induced an increase in endothelial cyclic GMP content that was reduced in the absence of extracellular calcium. 4. In cascade bioassay experiments using endothelial cells on microcarrier beads and perfused in columns, continuous infusion of bradykinin (0.1 microM) induced release of EDRF, assayed on rabbit aortic rings, that was maximal after 2 min and still detectable up to about 16 min. 5. In the presence of extracellular calcium, the time course of bradykinin (0.1 microM)-stimulated production of EDRF, assessed as endothelial cyclic GMP content was maximal within 1 min, declined thereafter, but was still significant after 30 min. Production of 6-keto PGF1 alpha, measured simultaneously rose rapidly but was complete within 3 min. 6. In the absence of extracellular calcium the resting endothelial content of cyclic GMP fell, but resting production of 6-keto PGF1 alpha was unaffected.(ABSTRACT TRUNCATED AT 250 WORDS)